2022
DOI: 10.33763/finukr2022.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to assessing the consequences of Russian military aggression and priorities for financial security of post-war reconstruction in Ukraine

Abstract: Introduction. The authors have examined existing approaches to assessing the consequences of Russian military aggression, certain aspects of the loss of Ukraine's economic potential, and plans for the post-war recovery and reconstruction, both national and with the participation of international partners. Problem Statement. Significant damage and destruction of infrastructure facilities are among serious consequences of the Russian-Ukrainian military conflict including significant reductions or negative values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This literature review underscores the significance of time series forecasting in understanding and predicting military casualties, exploring various methodologies across classical and machine learning approaches [11]. Techniques like ARIMA and machine learning methods such as SVR, KNN, and LSTM are evaluated, with simulation studies identified as valuable tools for informed decision-making [12]. Legislative attempts related to damage audits and compensation are discussed in addressing the repercussions of military activities, particularly in the context of Russian aggression [13].…”
Section: Related Workmentioning
confidence: 99%
“…This literature review underscores the significance of time series forecasting in understanding and predicting military casualties, exploring various methodologies across classical and machine learning approaches [11]. Techniques like ARIMA and machine learning methods such as SVR, KNN, and LSTM are evaluated, with simulation studies identified as valuable tools for informed decision-making [12]. Legislative attempts related to damage audits and compensation are discussed in addressing the repercussions of military activities, particularly in the context of Russian aggression [13].…”
Section: Related Workmentioning
confidence: 99%